A Natural Flavour in an Amphiphilic Association Structure - Suhaimi, Hamdan; Che Rose, Laili; Ahmad, Faujan (Universiti Putra Malaysia Press, 1995)
The miscibility ofa banana flavour, amyl acetate, in a water-in-oil microemulsion of water/sodium dodecyl sulphate (SDS): hexan-1-01 (35:65) in n-decane and fJ-xylene system was carried out at 30°e. The systems were tested by a phasestudy and refractometry method. The solubility of the flavour was observed to be connected to the ratio of SDS: hexan-1-D1 and hydrocarbon; a higher solubility of the flavour was observed in a larger ratio. The solubility was, however, inversely proportional to the water content.